The meaning of dancing aerobics during physical training of students of medical school - Johnson, Stephanie (Запорізький державний медичний університет, 2015)
The most popular, mass and popular type of motor activity among students in recent years have been aerobics and its variants. One of the most significant reasons for the decline of interest in aerobics respondents believe; excessive complexity of gymnastic complexes that for students who do not have a sufficient level of coordination abilities and motor experience, is an insurmountable obstacle.